Moving Beyond CSR - Exploring How Environmental Social Governance Creates Value for Firms as Well as Society Through the Mitigation of Climate Change. - Huntley, Alexander (2020)
Purpose This academic paper seeks to explore the relationship between climate change and the current business operations. It seeks to address the current issues with corporate social responsibility, suggesting that traditional approaches are not enough to successfully curve an organisation’s carbon emissions. As such, the paper seeks to outline a new framework; one which incorporates the Sustainable Responsible Investing (SRI) theory of Environmental Social Governance (ESG). This new framework is paired with existing business case studies, with the intention to highlight how organisations can address the issue of climate change, as well as create value for their organisation.